(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2010)
Results of the investigation of heavy metal (Cu, Pb, Ni, Mo, Zn, Ag) accumulation in leaves of some arboreous species of Yerevan, growing on soils with different degree of pollution by these elements are presented. White poplar has the highest resistance to pollution and the utmost extent of heavy metal accumulation (total concentrations of metals). C-values (amount of DNA contained within a haploid nucleus) of studied arboreous species have been obtained from electronic database. Certain correlation has been revealed between genome size of these species and their resistance to pollution with heavy metals. Species with small genome size and high degree of heavy metal accumulation can be recommended for implementation of biological monitoring and phytomelioration of polluted soils.